Hybrid incompatibility is consistent with a hybrid origin of Heliconius heurippa Hewitson from its close relatives, Heliconius cydno Doubleday and Heliconius melpomene Linnaeus (2004)
Shared ancestral variation and introgression complicates the reconstruction of phylogenetic relationships among closely related taxa. Here we use overall genomic compatibility as an alternative estimate of species relationships in a group where divergence is rapid and genetic exchange is common. Heliconius heurippa , a butterfly species endemic to Colombia, has a colour pattern genetically intermediate between H. cydno and H. melpomene : its hindwing is nearly indistinguishable from that of H. melpomene and its forewing band is an intermediate phenotype between both species. This observation has lead to the suggestion that the pattern of H. heurippa arose through hybridization. We present a genetic analysis of hybrid compatibility in crosses between the three taxa. Heliconius heurippa ?×?H. cydno and female H. melpomene ?×?male H. heurippa yield fertile and viable F1 hybrids, but male H. melpomene ?×?female H. heurippa crosses yield sterile F1 females. In contrast, Haldane's rule has previously been detected between H. melpomene and H cydno in both directions. Therefore, H. heurippa is most closely related to H. cydno , with some evidence for introgression of genes from H. melpomene. The results are compatible with the hypothesis of a hybrid origin for H. heurippa . In addition, backcrosses using F1 hybrid males provide evidence for a large Z(X)?chromosome effect on sterility and for recessive autosomal sterility factors as predicted by Dominance Theory.